ADMINISTRASI KEPENDUDUKAN BERDASARKAN UU NO. 24 TAHUN 2013 PERSPEKTIF SIYASAH SYAR’IYYAH (PENCATATAN KEMATIAN KABUPATEN GOWA) - Sahruni; Maloko, M Thahir (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
This study aims for Population Administration Based on Law no. 24 of 2013 Siyasah Syar’iyyah Perspective (Death Registration of Gowa Regency). In answering these problems, the author uses a normative syar`i approach and an empirical juridical approach. The method of data collection is done by way of interviews, observation, documentation. The results of the study indicate that the roles and responsibilities of the Gowa district government in the Population and Civil Registration Service in the population administration service for death registration have been going well but cannot be said to have been fulfilled. There are still many people who do not know the importance of arranging death certificates for people who have died due to the lack of outreach by the government to the community regarding population administration. This has an impact on public awareness regarding the management of death registration. As a result, the name cannot be removed from the Family Card and the data will remain active in the population database and of course it can be misused by irresponsible people. In the view of siyasa syar’iyyah the population and civil registration service has carried out the mandate as a responsibility in accordance with Q.S Al-Ahqaf/46:19, by improving the quality, facilities and infrastructure of population administration services.